Laboratory test and numerical simulation of laminated glass window vulnerability to debris impact - Zhang, X.; Hao, Hong; Ma, G. (Pergamon, 2013)
This paper presents results of laboratory tests and numerical simulations on the vulnerability of laminated glass windows subjected to windborne wooden block impact. Wooden debris weighing 2 kg, 4 kg and 8 kg with a velocity of 9 m/s to 35 m/s impacting on the glass windows is considered in this study. Performances of typical windows of sizes 2000 mm × 1100 mm and 1200 mm × 600 mm with 3 mm thick float glass plies laminated by 1.52 mm, 1.88 mm, 2.28 mm and 2.66 mm PVB interlayer are evaluated. It has been found that interlayer thickness plays a dominating role in the penetration resistance capacity of the laminated glass windows subjected to windborne debris impact. The vulnerability curves of laminated glass windows with various thicknesses and dimensions are generated. A predictive method based on laboratory observation is also developed to estimate glass fragments induced by debris impact. The fragment mass and launching speed are estimated with respect to the impact debris mass and velocity.